Comunicación digital y su influencia en la identidad cultural de los adolescentes del sector Viofa de la Parroquia San Camilo del cantón Quevedo, año 2022 - Garcia Guerrero, Emily Yustin (2022)
The present research project has as general objective: To analyze digital communication and its influence on the cultural identity of adolescents in the Viofa sector of the San Camilo parish of the Quevedo canton, year 202, the same one that served as a base source to be able to develop the various theoretical underpinnings of both variables, both dependent and independent. Therefore, various research formalities were used in turn, the observation technique and the questionnaire of questions was used as an instrument, which helped us to be able to determine the quantitative answers according to the population taken as a fundamental base 89 adolescents to be able to carry out the respective survey, through the Google Forms tool that allowed the survey to be developed immediately together with the virtual status. Digital communication today is part of everyday life for both adolescents and society in general, because it is based on the digital age where many users access various platforms and media to be able to communicate instantly and receive effective information. and immediate. Therefore, cultural identity symbolizes the patronage of each person, the same that hierarchizes the various cultural typologies, always mentioning their customs and traditions of each environment in which they work.